CERTAIN FAMILIES OF MULTIVARIABLE CHAN-CHYAN-SRIVASTAVA POLYNOMIALS - Ozarslan, M. A.; Srivastava, R.; Kaanoglu, C. (Univ Miskolc Inst Math, 2017)
In this paper we introduce r-parameter Srivastava polynomials in r-variable by inserting new indices. These polynomials include the Lagrange polynomials in several variables, which are also known as Chan-Chyan-Srivastava polynomials (W.-C.C. Chan, C.-J. Chyan and H.M. Srivastava, The Lagrange polynomials in several variables, Integral Transforms and Special Functions, 12 (2001) 139-148). We prove several two sided linear generating relations between r-variable and (r - 1)- variable Chan-Chyan-Srivastava polynomials. Some special cases of the main results are also presented.
Keywords: generating functions; Srivastava polynomials; Chan-Chyan-Srivastava polynomials